Pineapple Waste Cellulose Hydrogel: A Sustainable Absorbent for Drug Delivery System - Satria, Heri; Pandiangan, Kamisah Delilawati; Afriyani, Hapin; Alista, Diska Indah; Afiria, Arifah Rara; Nabila , Febiana (Trends in Sciences, 2025)
Cellulose-based hydrogels are valuable biomaterials used in drug delivery systems. Cellulose, a biopolymer found in sources like agricultural waste, is abundant in countries such as Indonesia. PT Bromelain Enzyme in Lampung Province generates roughly 20 tons of cellulose-rich pineapple core waste annually from bromelain extraction, providing significant raw material for hydrogel production. This study explored the feasibility of using this waste for synthesizing hydrogels and assessing their potential as drug-delivery agents through various experiments. TAPPI methods for composition analysis revealed 38.5% cellulose, 25.05% hemicellulose and 12.99% lignin in the waste. The isolation of mangrove actinomycetes on ISP 2 medium identified the ActM-DMB 7 isolate, which displays high xylanolytic activity. This isolate was utilized in bio-pretreatment to remove amorphous portions, yielding highly crystalline cellulose with an increased crystallinity index from 16.68 to 33.35. Cellulose resizing showed a bimodal distribution of particle diameters at 0.657 and 1.832 µm. Hydrogel production utilized grafting, confirmed by FTIR analysis with characteristic N-H (3,183.14 cm−1) and C=O (1,647.48 cm−1) amide bands. The product was examined for absorption and delivery potential of ascorbic acid and amoxicillin, exhibiting a high swelling ratio (plateauing at ~34 Sg/g) and significant water retention over 10 h. The hydrogels efficiently absorbed and released ascorbic acid and amoxicillin, with amoxicillin showing antibacterial effects against Escherichia coli and Staphylococcus aureus. This research emphasizes valuing pineapple processing waste for sustainable, economically viable functional hydrogels for biomedical applications, including drug delivery, aligning with circular economy principles by transforming an industrial byproduct into a high-value material. HIGHLIGHTS Enzymatic cellulose isolation from pineapple core waste was achieved using novel xylanase- and cellulase- producing ActM-DMB 7 isolate sourced from mangrove sludge. This bio-derived cellulose was then expertly crafted into functional hydrogels through polyacrylamide grafting. The synthesized hydrogels were then rigorously tested and proven effective for absorbing and potentially delivering both vitamin C and amoxicillin. GRAPHICAL ABSTRACT